ROSE MOTIF IN THE WORK OF SALVADOR DALI - Михайлова, Рада Дмитрівна; Булгакова, Тетяна Володимирівна (Art and Design, 2024)
Purpose: analyze the work of S. Dalí "Meditating Rose"; to reveal its generalized figurative meanings as a reflection of the objective (change in worldview paradigm in the post-war period) and subjective (creative methods of the surrealist artist) qualities of the artistic process of the middle of the 20th century. The research is based on socio-cultural, comparative historical, historical-theoretical, empirical methodology, methods of analysis, synthesis, modeling/assumptions are also used. The analysis of Salvador Dalí's work "Meditating Rose" (1958) reflects the changes in the social life of the European community, which were reflected in the philosophical-worldview plan. In the art of the avant-garde, this process found expression in the works of surrealism, where the content load is shifted towards meaningful formulas capable of conveying that which in real life has been abandoned. In S.Dali's work, the canvas turns into an object, the specifics of which are the layering of ideas, controversiality, emotional contrast, shockingness, multiple polyphony, interweaving of concepts. At the same time, the artist himself appears in the dynamics of the search for his own identity, actualized through the function of the artist-moderator of culture. Against this background, the interpretation of the rose motif in S. Dalí's work appears as a result of the evolution of traditional themes of artistic culture, which changed the semantic interpretations from the desire to visualize the realities of being to the desire to abstract from realities according to the formula-sign. The analysis of Salvador Dalí's work "Meditating Rose" (1958) reflects the changes in the social life of the European community, which were reflected in the philosophical-worldview plan. In the art of the avant-garde, this process found expression in the works of surrealism, where the content load is shifted towards meaningful formulas capable of conveying that which in real life has been abandoned. In S.Dali's work, the canvas turns into an object, the specifics of which are the layering of ideas, controversiality, emotional contrast, shockingness, multiple polyphony, interweaving of concepts. At the same time, the artist himself appears in the dynamics of the search for his own identity, actualized through the function of the artist-moderator of culture. Against this background, the interpretation of the rose motif in S. Dalí's work appears as a result of the evolution of traditional themes of artistic culture, which changed the semantic interpretations from the desire to visualize the realities of being to the desire to abstract from realities according to the formula-sign. Scientific novelty of the research consists in the study of S. Dali's work "Meditational Rose" as an artistic response of the surrealist artist to the worldview-meaningful and social-political changes of the middle of the 20th century. Practical significance of the study is due to the deepening of the skills of working with the material of modernist art of the 20th century, namely, examples of the surrealist stylistic direction. The materials of the work can be used in the educational process and practical activities of artists and designers as an example of the interpretation of a pictorial plant motif that has a long history of use.